Chitosan‐Coated Glass Beads in a Fluidized Bed for Use in Fixed‐Bed Dye Adsorption. Issue 4 (22nd February 2021) - da Silva Alves, Daniele Costa; Capa Verde Pires, Roni Anderson; Algã, Francine Fonseca Diniz; Gonçalves, Janaina Oliveira; Dotto, Guilherme Luiz; de Almeida Pinto, Luiz Antonio; Felipe, Carlos Alberto Severo
Abstract: The effects of the inlet air temperature and two chitosan solutions, pure or with coating auxiliaries, on the coating efficiency of glass beads in a fluidized bed were analyzed. The coated beads were used in a fixed‐bed column for adsorption of reactive black 5 dye in aqueous solution, and the effects of the pH and the coating solution formulation on the adsorption capacity were investigated. The glass bead coating process reached higher efficiencies at an air temperature of 80 °C with pure chitosan solution. The highest adsorption capacities were found at pH 3, using the beads coated with pure chitosan solution. All dynamic adsorption models were suitable to represent the breakthrough curves. The high values found for the coating efficiency and adsorption capacity prove these methods to be promising in dye adsorption. Abstract : The effects of the inlet air temperature and chitosan solution composition on the coating efficiency of glass beads in a fluidized bed were analyzed and the coated beads were used for RB5 dye adsorption. The highest adsorption capacities were achieved at pH 3 when using the beads coated with pure chitosan solution. Three dynamic adsorption models can be applied to represent the breakthrough curves.